Towards a Sustainable Energy Future: A Case Study of Luxembourg’s Transition to Renewable Energy and Carbon Neutrality - Oberhausen Krippler,Felix (2023)
Climate change poses a significant threat to humanity, with devastating consequences already occurring. Transitioning to a low-carbon economy is crucial for mitigating the effects of climate change. High per capita energy consumption and emissions make this transition an urgency for Luxembourg. This study focuses on the sustainable energy transition in Luxembourg, examining challenges and opportunities through a case study. To accelerate the transition, policymakers must implement closer regulation of energy types and provide subsidies and tax reductions for renewable energy adoption. Accountability for energy consumption and emissions should apply to both industries and individuals, with incentives to encourage their participation. Transforming the transportation sector is crucial. Collaboration beyond national borders is necessary due to limited land availability and a stance against nuclear energy and carbon capture technology. Luxembourg's progress in renewable energy transition has been comparably slow. Achieving a successful transition within Luxembourg alone may be challenging by 2050. Integration of individuals into the transition is vital for its success. Changing the low tax rate on fuels to match neighbouring countries can significantly reduce fossil fuel consumption and incentivize electric vehicle adoption. By embracing renewable energy and engaging stakeholders, Luxembourg can contribute to mitigating climate change. However, more work is needed to ensure a sustainable energy future for the country.
Keywords: Renewable energy; emissions; electric vehicles; carbon neutrality; mitigation